The implantable cardiac monitor in heart failure patient: a possible new indication?. (26th April 2023) - Cicogna, Francesco; Lanza, Oreste; Monzo, Luca; Tota, Claudia; Cice, Gennaro; De Ruvo, Ermenegildo; Calò, Leonardo
Abstract: Implantable cardiac monitors (ICMs) have found increasing use in clinical practice over the years, proving, when used in high-risk populations, to facilitate the diagnosis of bradyarrhythmias and tachyarrhythmias requiring treatment. Experience with heart failure patients undergoing pacemaker (PMK) or implantable defibrillator (ICD) implantation, which allow for continuous electrocardiographic monitoring and transthoracic impedance assessment, has made it possible to identify predictors of heart failure flare-ups. In this context, the use of telemonitoring has been shown to ensure better management of patients with heart failure. These benefits cannot be assessed to date in patients with heart failure and left ventricular ejection fraction (LVEF) > 35% who have no indication for PMK or ICD implantation. This population has been shown to have a significant incidence of ventricular arrhythmias and bradyarrhythmias. In addition, a significant number of cerebrovascular events are observed in this population, largely attributable to the high incidence of atrial fibrillation (AF). In this population, the occurrence of AF has also been shown to have a negative impact on patients' prognosis; at the same time, a rhythm control strategy has been shown to be more beneficial in this area than a rate control strategy. Studies also suggest arrhythmias have a negative impact on the cognitive status and quality of life of heart failure patients. These reasons could justify the implantation of ICMs equipped with telemonitoring systems in heart failure patients. The information provided by the monitoring system, if properly managed, could bring benefits in terms of prognosis and quality of life along with a reduction in economic costs. We will try here, by answering a few questions, to assess whether there is an indication for ICM in heart failure, which patients should be candidates and how these patients should be managed.